Firm Financing and Growth in the Arab Region - Lorente, Juan Jose Cortina (World Bank E-Library Archive, 2016)
This paper documents how firms in Arab countries issue equity, corporate bonds, and syndicated loans in domestic and international markets to obtain financing and grow. Using a new data set on issuance activity and firm performance, the paper finds that capital raising through these markets has grown rapidly since the early 1990s and involved an increasing number of issuing firms. Whereas the amounts raised (relative to gross domestic product) in equity and loan markets stand well with respect to international standards, bond issuance activity lags behind. Yet, bond financing has gained importance over time. Equity issuances primarily take place domestically, while bonds and loans are mostly issued internationally, display long maturities, and entail low levels of credit risk. Issuing firms are larger, grow faster, and are more leveraged than non-issuers. While issuers tend to be larger ex ante than non-issuers, the size gap between them seems to widen over time